Enter the expression that is equivalent to −34(24−12x).

Enter your answer as a simplified expression, like this: 42x+53


Please help me!!!

Respuesta :

Answer:

The given expression is  simplified as : −34 (24 − 12 x)  =  -816 + 408 x

Step-by-step explanation:

The given expression is given as:

−34 (24 − 12 x)  

Now, by DISTRIBUTIVE PROPERTY:

A( B -C) = AB - AC

Applying the same distributive property in the given expression ,we get

−34 (24 − 12 x)  =  (-34) (24) - (-34)(12 x)

                          =  -816 + 408 x

or, −34 (24 − 12 x)  =  -816 + 408 x

Hence, the given expression is simplified as  

  −34 (24 − 12 x)  =  -816 + 408 x